Health providers’ opinions on provider–client relations: results of a multi-country study to test Health Workers for Change - Fonn, S; Mtonga, AS; Nkoloma, HC; Bantebya Kyomuhendo, G; Dasilva, L; Kazilimani, E; Davis, S; Dia, R (Health Policy and Planning, 2001)
A multi-centre study in four African countries was undertaken to test the acceptability and effectiveness of Health Workers for Change, a methodology to explore provider–client relations within a gender-sensitive context. This intervention addresses the interpersonal component of quality of care. The methodology, consisting of six workshops, was implemented by research teams in Zambia, Senegal, Mozambique and Uganda. It was found to be acceptable within in a range of cultural and primary health care settings. The workshops allowed difficult issues such as prejudice and bribery to be discussed openly, fostered problem solving and the development of practical plans to address problems that could strengthen district health systems.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; health - dignified care / saúde - atendimento humanizado / mau atendimento; health / saúde

From ‘Abaixo’ to ‘chiefs of production’: Agrarian change in Nampula province, mozambique, 1975–87 - Dinerman, Alice (The Journal of Peasant Studies, 2001)
This article reconstructs key aspects of the evolving relationship between state institutions and former regulos (Portuguese‐appointed chiefs), in Nampula Province, Mozambique during the first 12 years of independence. In doing so, it simultaneously draws on and critiques two opposing interpretations of revolution and counterrevolution which have dominated scholarly production on post‐independence Mozambique and have polarized Mozambican studies in recent years. Against both sets of literature, my study finds that state socialism did not always and everywhere bring major disruptions to grassroots structures of authority; rather, many families who had been recognized by the Portuguese as royals were able, through a variety of strategies, to maintain their grip on local power. Secondly, I argue that the provincial government's enlistment of former regulos to serve as ‘chiefs of production’ was but one aspect of an attempt on the part of officialdom to recreate the most salient aspects of the colonial cotton regime rather than a war‐induced genuflection by the Frelimo regime to Renamo on the question of chiefly rule, as has been claimed by what I call ‘revisionist’ scholarship. Frelimo's refusal to acknowledge the role of villagization in agricultural decline throughout the country, a point raised and highlighted by revisionist writing is, however, crucial to understanding the ideological practices that helped justify and legitimate the return to Portuguese precedent on matters relating to rural labour. The reasons why Nampula was the site of these initiatives are explored.
Publisher: Routledge _eprint: https://doi.org/10.1080/03066150108438766
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; agriculture / agricultura; authority / autoridade

A study of the actual and potential usage of information and communication technology at district and provincial levels in Mozambique with a focus on the health sector - Braa, Jørn; Macome, Esselina; Mavimbe, João Carlos; Nhampossa, José Leopoldo; da Costa, João Leopoldo; José, Bonifacio; Manave, Aurélia; Sitói, António (The Electronic Journal of Information Systems in Developing Countries, 2001)
This article presents results from a study on the use and appropriation of information and communication technologies (ICT) in Mozambique with a focus on the health sector. The three provinces of Gaza, Inhambane and Niassa were surveyed and two questionnaires addressing 1) computer users and their ability to manage ICT, and 2) health workers and their handling of health information, were used. Based on this study appropriate strategies for developing an ICT-infrastructure with the needs of the health sector as points of departure are discussed. The study is born out of a program to strengthen and further develop the health information and management systems at district and provincial levels as part of a process to support decentralisation of the health system in Mozambique. The study shows that computers and Internet are rapidly being spread to the provincial capitals and major districts in Mozambique. A main problem identified is the lack of ICT-skills and education and poorly developed infrastructure and networks of support. There are very few formal ICT companies providing hardware, and even less, software support. Maintenance and learning about ICT are to a large extent going on within informal networks of computer users in the provinces. A main finding in this study is that development of ICT capacity and information systems at district and provincial levels in Mozambique needs to be an integrated effort across sectors. A district health information system cannot be developed in a void. A general recommendation is to develop educational programmes ranging from training of ICT entrepreneurs and health workers and managers, to Masters and PhD programmes in ICT and health information systems. A specific recommendation related to health information systems development is to focus on the district level and to develop a strategy which encompasses and integrates all districts, both the advanced districts with computers and the majority of the districts where there are no computers.
Publisher: Wiley Online Library
Keywords: *indexed; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; health - health information systems / saúde - sistema de informação de saúde; health / saúde

The Indonesian Financial Crisis: From Banking Crisis to Financial Sector Reforms, 1997-2000 - Sharma, Shalendra D. (Cornell University Press, 2001)
In mid-1998, a World Bank study grimly noted that "Indonesia is in deep economic crisis. A country that achieved decades of rapid growth, stability, and poverty reduction is now near economic collapse . . . no country in recent history, let alone one the size of Indonesia, has ever suffered such a dramatic reversal of fortune." There is bitter irony in Indonesia's fall from grace. Long hailed as a model of successful economic development, it was widely predicted to escape the fate of Thailand. Between June-August 1997, as Thailand's economy unraveled and the virulent Asian flu sent shock waves through the region, the Indonesian economy remained relatively stable—a veritable rock in the stormy sea. Even the World Bank remained upbeat about the short-term outlook, believing that a widening of the intervention band would be sufficient to ward off contagion.4 The Indonesian government, which received much praise for its swift and decisive response to the crisis, went to great lengths to assure jittery investors "that Indonesia was not Thailand." Then the unthinkable happened. Indonesia suddenly succumbed to the contagion, and, measured by the magnitude of currency depreciation and contraction of economic activity, it emerged as the most serious casualty of Asia's financial crisis. What happened? Why did Indonesia (and the other high-performing Asian economies) collapse like hollow dominoes? In the numerous post-mortems that have followed, analysts have identified a number of related factors behind the region's dramatic reversal of fortune. In the case of Indonesia, the variable that soon acquired particular salience was "crony capitalism." Initially popularized by the Economist, the term quickly took a life of its own. Soon thereafter, the distinguished MIT economist, Paul Krugman, would argue that crony capitalism lay the root of Indonesia's—and indeed, East Asia's—financial woes. Krugman describes the innerworkings and manifestations of the insidious crony capitalism in evocative prose.
Number: 71 Publisher: Southeast Asia Program Publications at Cornell University
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico